Proof of concept pilot study: prevalence of grass virus infection and the potential for effects on the allergenic potency of pollen - Howarth Peter H; Cooper J Ian; Lau Laurie CK; Bodey Kathleen; Edwards Mary-Lou; Soh Emily; Pallett Denise W; Walls Andrew F; Wang Hui (BMC, 2009)
Abstract Background Wild plants harbour a variety of viruses and these have the potential to alter the composition of pollen. The potential consequences of virus infection of grasses on pollen-induced allergic disease are not known. Methods We have collected pollen from Dactylis glomerata (cocksfoot; a grass species implicated as a trigger of allergic rhino-conjunctivitis) from Wytham Wood, Oxfordshire UK. Extracts were prepared from pollen from uninfected grass, and from grass naturally infected by the Cocksfoot streak potyvirus (CSV). Preparations of pollen from virus-infected and non-infected grasses were employed in skin testing 15 grass pollen-allergic subjects with hayfever. Allergen profiles of extracts were investigated by Western blotting for IgE with sera from allergic subjects. Results The prevalence of CSV infection in cocksfoot grasses sampled from the study site varied significantly over an eight-year period, but infection rates of up to 70% were detected. Virus infection was associated with small alterations in the quantities of pollen proteins detected by polyacrylamide gel electrophoresis, and in the patterns of allergens identified by Western blotting with IgE from grass pollen allergic subjects. For individual subjects there were differences in potencies of standardised extracts of pollen from virus-free and virus-infected plants as assessed by skin testing, though a consistent pattern was not established for the group of 15 subjects. Conclusion Infection rates for CSV in cocksfoot grass can be high, though variable. Virus-induced alterations in components of grass pollen have the potential to alter the allergenic potency.